Compliance: Conceptualizing, Measuring, and Explaining Adherence to Judicial Rulings. Issue 4 (7th September 2012) - Kapiszewski, Diana; Taylor, Matthew M.
<x xml:space="preserve">Abstract</x> Public authorities' compliance with judicial dictates is central to legality and constitutionality, may influence broader policy and political outcomes, and can have powerful feedback effects on judicial decision making, independence, and power. As such, it has crucial implications for interbranch relations and the rule of law. Effectively measuring compliance with judicial rulings and clearly explaining when and why elected leaders adhere to courts' mandates present a range of inferential challenges. Building on the groundwork laid in the burgeoning literature on the topic, this article advances two analytic frameworks (one for measuring and one for explaining compliance), offers strategies for grappling with the problems of descriptive and causal inference that arise in studying compliance, and advocates the use of multiple analytic methods to generate and test hypotheses regarding compliance.